„Skazani na samotność?” O konsekwencjach izolacji społecznej w wybranych jej kontekstach - Skibińska, Bożena (Studia Edukacyjne, 2020)
Today, disturbingly often, it is possible to witnesses the effects of stigma and exclusion not only of the individual, but of whole groups of people, the result of reinforced, persistent stereotypes and prejudices about the subjects mentioned. They cause wrong social attitudes, expressed by the deprivation of the isolated persons of their rights to create and nurture relationships based on closeness and love, and often doom these people to a life of total seclusion. This article is an attempt to show the far-reaching consequences of depriving persons with intellectual disabilities and denying the right of self-expression. It is also a critical reflectionon the irregularities experienced by people, towards whom it is introduced, in terms of institutional isolation. At the same time, by presenting the results of personal research and conclusions, attention is being drawn to the fact that in our society there is an emerging hope for positive changes in the daily treatment of the socially isolated individuals. Yet, there is a constant need for a continuous reinforcement of the public awareness of the fact that the reintegration of these excluded individuals in the community benefits both the parties involvedTaking up the theme of stigma and social exclusion of persons with intellectual disabilities and convicts is considered important and relevant, as this is an issue which remains topical and gives rise to multiple moral dilemmas.